Stress dan Strategi Coping Remaja Perempuan: Sebuah Fenomena Psikososial di Era Milenial - Forletus Panggah Utama (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This study aims to look at coping strategies in in female adolescent, which is a psychosocial phenomenon in the millennial era. The setting of this study was in SMA 1 Wanadadi. This study included quantitative descriptive research with a sample of 200 female adolescent respondents. The results of this study indicate that the coping strategies of female adolescents in SMA 1 Wanadadi are in the good category. Can be analyzed from various aspects, in the aspect of self-activity, female adolescent have a good level of coping strategies in themselves. in the aspect of planning, female adolescent have very good category, as well as in the aspect of seeking social support, female adolescent have a way to find solutions to their problems. Very good results are also seen in the religious aspect, female adolescent have had a good level of surrender for the problems they are experiencing to God, so they have a better life calm. But in some aspects it still shows a low level of coping strategies, in the aspects of self-control and acceptance. self-control and emotions in adolescent girls are still low when there are problems. and they also have not been able to accept sincerely the reality of their lives/problems. The conclusion of this research is that female adolescent in SMA 1 Wanadadi have a good coping strategy. Coping strategies are ways that individuals use to solve problems, overcome changes that occur and threatening situations both cognitively and behavior.